2017
DOI: 10.1080/13803395.2017.1278746
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age on the learning and forgetting of primacy, middle, and recency components of a multi-trial word list

Abstract: The serial position effect reveals that recall of a supraspan list of words follows a predictable pattern, whereby words at the beginning (primacy) and end (recency) of a list are recalled more easily than words in the middle. This effect has typically been studied using single list-learning trials, but in neuropsychology, multi-trial list-learning tests are more commonly used. The current study examined trends in learning for primacy, middle, and recency effects across multiple trials in younger and older age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…A number of studies, however, addressed the retention of practice related gains in task performance in older adults in comparison to younger adults (Shea et al, 2006; Fraser et al, 2009; Nemeth et al, 2010; Wilson et al, 2012). While younger adults were able to retain training-related gains for long periods of time (across time intervals with no additional training), the passage of time (with no additional training afforded) was found to adversely affect the performance gains in older adults (Malone et al, 2016; Griffin et al, 2017). It was concluded that long intervals of no training may lead to forgetting and skill attrition, the loss of gains previously acquired, in the elderly (Malone et al, 2016; Griffin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies, however, addressed the retention of practice related gains in task performance in older adults in comparison to younger adults (Shea et al, 2006; Fraser et al, 2009; Nemeth et al, 2010; Wilson et al, 2012). While younger adults were able to retain training-related gains for long periods of time (across time intervals with no additional training), the passage of time (with no additional training afforded) was found to adversely affect the performance gains in older adults (Malone et al, 2016; Griffin et al, 2017). It was concluded that long intervals of no training may lead to forgetting and skill attrition, the loss of gains previously acquired, in the elderly (Malone et al, 2016; Griffin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…While younger adults were able to retain training-related gains for long periods of time (across time intervals with no additional training), the passage of time (with no additional training afforded) was found to adversely affect the performance gains in older adults (Malone et al, 2016; Griffin et al, 2017). It was concluded that long intervals of no training may lead to forgetting and skill attrition, the loss of gains previously acquired, in the elderly (Malone et al, 2016; Griffin et al, 2017). The current results suggest that perhaps as a default, the motor system of older adults may treat motor “how to” knowledge that is not in continuous use as less prioritized for long-term retention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that semantic encoding is automatic in verbal short-term memory (Campoy et al, 2015). Furthermore, the recency effect, which plays a significant role in RAVLT scores, is largely driven by verbal attention (Griffin et al, 2017). The recency effect has been conceptualized in immediate free recall as implicit learning coupled with a particular mode of retrieval that may, but need not, be conscious and explicit (Baddeley and Hitch, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…(Bower, 2000). V současnosti se v této tradici pokračuje a při zkoumání zmíněné problematiky jsou využívány především testy seznamů slov, jejichž počátek sahá již do 19. století, kdy Binet a Henri (1894) publikovali několik experimentů zkoumajících paměť prostřednictvím seznamů slov (Griffin et al, 2017). Jednotlivé metody používané pro tyto účely se mohou lišit ve způsobu administrace jednotlivých fází, což je přehledně zobrazeno v tabulce č.…”
Section: úVodunclassified